An integrated fuzzy-lp approach for a supplier selection problem in supply chain management - Guneri, Ali Fuat; Yucel, Atakan; Ayyildiz, Gokhan (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In supply chain management process, the firm select best supplier takes the competitive advantage to other companies. Thus, supplier selection is an important issue and with the multiple criteria decision-making approach, the supplier selection problem includes both tangible and intangible factors. This paper is aimed to present an integrated fuzzy and linear programming approach to the problem. Firstly, linguistic values expressed in trapezoidal fuzzy numbers are applied to assess weights and ratings of supplier selection criteria. Then a hierarchy multiple model based on fuzzy set theory is expressed and fuzzy positive and negative ideal solutions are used to find each supplier's closeness coefficient. Finally, a linear programming model based on the coefficients of suppliers, buyer's budgeting, suppliers' quality and capacity constraints is developed and order quantities assigned to each supplier according to the linear programming model. The integrated model is illustrated by an example in a textile firm. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Supplier selection; Fuzzy set theory; Multiple criteria decision-making; Linear programming; CRITERIA; Computer Science; Engineering; Operations Research & Management Science